2021
DOI: 10.1177/0269215521995185
|View full text |Cite
|
Sign up to set email alerts
|

Description of content, structure and theoretical model of a group-based pain management programme in the treatment of patients with persistent non-specific low back pain and psychological risk factors in a secondary sector setting

Abstract: Objective: To present the theoretical foundation and methodological considerations for a group-based pain management programme for patients with persistent non-specific low back pain and psychosocial risk factors. Method: The Template for Intervention Description and Replication (TIDieR) checklist was used as a framework for describing the content, structure and context of the program. The theoretical rationale underlying the pain management programme was described using the first three steps of the Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A detailed description of the intervention design and rationale has been published elsewhere, to enable replication of the study and to facilitate comparison across studies. 18 Although previous studies have shown that non-psychologists can indeed deliver psychological interventions to manage low back pain effectively, 40 we chose to let a psychologist supervise the physiotherapists and nurses delivering the intervention to ensure the therapeutic quality. This approach is in line with the recommendations put forward in a systematic review by Hall et al stating that cognitive behavioural therapy providers should undergo training in order to secure a high level of treatment fidelity, and therefore, healthcare professionals are recommended to engage in initial training or supervision by experienced psychologists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the intervention design and rationale has been published elsewhere, to enable replication of the study and to facilitate comparison across studies. 18 Although previous studies have shown that non-psychologists can indeed deliver psychological interventions to manage low back pain effectively, 40 we chose to let a psychologist supervise the physiotherapists and nurses delivering the intervention to ensure the therapeutic quality. This approach is in line with the recommendations put forward in a systematic review by Hall et al stating that cognitive behavioural therapy providers should undergo training in order to secure a high level of treatment fidelity, and therefore, healthcare professionals are recommended to engage in initial training or supervision by experienced psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…The details and theoretical foundation for the intervention has been published elsewhere. 18 In brief, the programme consisted of six group-based sessions each lasting two hours, spanning a time-frame of three months in total. All sessions were delivered face-to-face at the Spine Center.…”
Section: Description Of Usual Care and Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TIDieR framework can be used to describe the main features of an intervention, which is key to understanding and supporting implementation (Hoffmann et al, 2014). The TIDieR framework has been applied to describe the content and contexts of interventions from group‐based pain management interventions (Skovbo et al, 2021), to population health and policy interventions (Campbell et al, 2018). The AACTT framework specifies behaviours by Actor, Action, Context, Target and Time and supports research and intervention development by identifying who needs to do what differently by specifying behaviours (Presseau et al, 2019).…”
Section: Introductionmentioning
confidence: 99%